2017
DOI: 10.7759/cureus.997
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome After Decompressive Craniectomy in Patients with Dominant or Non-Dominant Malignant Middle Cerebral Infarcts

Abstract: Background: The use of decompressive craniectomy (DC) has been studied in the setting of different conditions, including traumatic brain injury, subarachnoid hemorrhage, and malignant middle cerebral artery (MCA) infarction. The rationale of this study is to determine the functional outcome after DC in patients with malignant MCA infarcts.Methods: A longitudinal cohort study was performed based on patients diagnosed with malignant MCA territory infarction admitted to the Neurosurgery Department of a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…[2,3] DC has been used to treat severe intracranial hypertension secondary to various causes. [4] This involves removal of a part of the calvarium, with or without duraplasty to create extra volume for intracranial contents thereby reducing ICP. [5] DC may improve oxygen delivery to brain cells by improving blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] DC has been used to treat severe intracranial hypertension secondary to various causes. [4] This involves removal of a part of the calvarium, with or without duraplasty to create extra volume for intracranial contents thereby reducing ICP. [5] DC may improve oxygen delivery to brain cells by improving blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Pakistan (47) showed that DC is beneficial in both dominant and non-dominant side infarctions. In this study the mean surgery time from diagnosis was 60.61 h, which is beyond the recommended period (within 24–48 h).…”
Section: Resultsmentioning
confidence: 99%
“… 19 Alam et al only reported a poor functional outcome (mRS >4) in patients undergoing DC with total mortality of 8.7%. 20 In Kürten series, in a 3-month follow-up, 44.6% of surgically treated patients showed moderate–severe disability (mRS 4), while 32.6% suffered a poor outcome (mRS 5). 21 In our series of 14 patients, affected by malignant MCA and underwent DC, a favourable mRS (mRs 0–3) at 9 months of follow-up was recorded in 5 patients (41.6%), while a poor functional outcome was evidenced in 7 patients (58.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Gulensoy et al states that a preoperative GCS score of 7 or less than 7 does not allow to obtain favourable results 19. Alam et al only reported a poor functional outcome (mRS >4) in patients undergoing DC with total mortality of 8.7% 20. In Kürten series, in a 3-month follow-up, 44.6% of surgically treated patients showed moderate–severe disability (mRS 4), while 32.6% suffered a poor outcome (mRS 5) 21.…”
Section: Discussionmentioning
confidence: 99%